PVT1 depletion protects cartilage ATDC5 cells against LPS-induced inflammatory injury by regulating the miR-24/ADAMTS5 axis. Issue 65 (7th November 2018) - Li, Wenjun; Liu, Gejun; Wu, Xing
Abstract : Osteoarthritis is a common chronic arthritis among adults and cartilage dysfunction is largely responsible for osteoarthritis development. Abstract : Background : Osteoarthritis is a common chronic arthritis among adults and cartilage dysfunction is largely responsible for osteoarthritis development. Long noncoding RNAs (lncRNAs) have been reported to be related to osteoarthritis progression. However, the mechanism that underlies the effect of lncRNA plasmacytoma variant translocation 1 (PVT1) on inflammatory injury in cartilage ATDC5 cells remains elusive. Methods : The quantity of PVT1 and microRNA-24 (miR-24) was detected in human cartilage ATDC5 cells after transfection of si-PVT1, si-con, PVT1 or pcDNA and lipopolysaccharide (LPS) treatment for 12 h. Inflammatory injury was investigated using cell viability, apoptosis and secretion of inflammatory cytokines. The interaction of miR-24 with PVT1 or a disintegrin-like metalloproteinase with thrombospondin motifs 5 (ADAMTS5) was probed by bioinformatics, luciferase activity, RNA pull down and Ago1 RNA immunoprecipitation (RIP) assays. The effect of PVT1 and miR-24 on ADAMTS5 expression was evaluated in ATDC5 cells by western blotting (WB). Results : Treatment of LPS induced elevated PVT1 and reduced miR-24 expression in ATDC5 cells. Moreover, LPS inhibited cell viability, increased apoptosis and inflammatory cytokine production. However, PVT1 depletion attenuated LPS-induced inflammatory injury in ATDC5 cells. In addition, miR-24 directly bound to PVT1 and its deficiency reversed the effect of PVT1 deletion in LPS-treated ATDC5 cells. Furthermore, ADAMTS5 was a target of miR-24 and aberrant expression of ADAMTS5 was regulated by PVT1 and miR-24. Conclusion : PVT1 abrogation protected against LPS-induced inflammatory injury in ATDC5 cells by coordinating with the miR-24/ADAMTS5 axis, opening up a novel avenue for osteoarthritis therapeutics.